Microbial Leakage at Morse Taper Conometric Prosthetic Connection: An In Vitro Investigation. Issue 5 (October 2017) - Bressan, Eriberto; Stocchero, Michele; Jimbo, Ryo; Rosati, Claudio; Fanti, Elena; Tomasi, Cristiano; Lops, Diego
Abstract : Objective: To evaluate in vitro the sealing capability at the prosthetic connection interface of 2 conometric systems. Materials and Methods: Two conometric systems with the same design and different material were used, for a total of 24 samples. Each sample was assembled by a tapered abutment and respective coping. In group A, the copings were made of gold, whereas in group B they were made of PEEK. Three μL of mix bacterial suspension ( Aggregatibacter actinomycetemcomitans, Porphyromonas gingivalis, and Fusobacterium nucleatum species) was inoculated into the abutment screw hole, and the coping was inserted on the abutment. Samples were immersed into culture tubes and incubated for 24, 48, and 72 hours into anaerobic conditions. Visual evaluation of turbidity was performed at each time point. Qualitative-quantitative assessment using real-time polymerase chain reaction was performed at 72 hours. Any difference between the groups was checked by means of Fisher exact test. Results: Microbial leakage occurred in both groups, and there was no statistically significant difference between groups. Microbial concentration resulted in a presence inferior to 1 × 10 2 copies/μL in all positive assemblies. Conclusions: Because of the low bacterial count, it can be concluded that a minimal bacterial infiltration may be allowed by conometric interfaces for prosthetic connection.